The ENTHRONE 2 metadata management tool (MATool) (WISE 2008 MATool Demonstration) - Lugmayr, Artur (2008)
There are many metadata standards, and many more are to emerge - and many more metadata systems have to deal with. To cope with the challenge of the management of metadata generated and various sources, in many arbitrary formats, and for different purposes, a metadata management solution is required. This research work describes the MATool, as metadata management tool developed within the IST IP ENTHRONE 2. The tool provides metadata aggregation, metadata collection, and metadata conversion capabilities in the context of end-to-end Quality of Service (QoS) integrated management system for audio-visual services. The live demonstrator of the MATool were available at WISE 2008. © 2008 IEEE.